Updates on Management of Helicobacter pylori Infection and Antibiotic Resistant Helicobacter Infection Management - Nursyirwan, Saskia Aziza; Simadibrata, Marcellus (The Indonesian Society for Digestive Endoscopy, 2022)
H. pylori is a common human pathogen and it is estimated that approximately 50% of the world's population are infected. Furthermore it's prevalence infection in Indonesia is 20% but much higher among several ethnic groups (Papuans 42.9%, Batak 40.0%, and Bugis 36.7%). H. pylori’s growth and survival has been shown to be sensitive to a variety of antimicrobial agents. The success of the treatment depends on susceptibility, dosage, formulation, dose frequency, the use of adjuvants such as anti-secretory drugs, antacids or probiotics, and duration of treatment. The treatment for H. pylori infection keep evolving and the triple therapy, levofloxacin, was replaced by CLR in triple therapy for 14-day with eradication rates over 90%. Sequential therapy, also achieved a higher cure rate against clarithromycin-resistant strains than a 7 and 10 day triple therapy. Triple bismuth therapy and quadruple bismuth therapy are used less frequently due to their inherent complexity, the large number of tablets four times a day, side effects, and lack of support from pharmaceutical companies. Inclusively, vonoprazan is also a good choice that is fully effective from day one. The role of the probiotics is unclear and is not recommended in consensus groups. Two mucolytic agents, erdosteine and N-acetylcysteine (NAC), were found to increase it's eradication efficiency clinical trials when administered in supplementation with triple therapy but are not commonly used because of the need for high doses, and increased medical costs. therefore, H. pylori resistant management should be adapted to the results of the the culture of resistance and the guidelines of existing resistance patterns.